Analisis Pengaruh Kualitas Layanan Mobile Banking terhadap Kepuasan dan Loyalitas Nasabah pada Pengguna Layanan BRI Mobile Bank Rakyat Indonesia di Kantor Cabang Cirebon - Fajar Akbar Hariansyah; Niken Hendrakusma Wardani; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The purpose of this research is to determine influence of BRI Mobile service quality on customer satisfaction and loyalty of Bank Rakyat Indonesia in Cirebon region. 87 respondents were used as samples from BRI Mobile user in Cirebon region and sampling technique use purposive sampling. E-S-Qual and E-Recs-Qual model are used become primary model in this research. The model has been modified to adjust with this research object. The collection of data is obtained from disseminate questionnaire and data analysis use multiple linear regression and Kendall-Tau. The result from this research show that simultaneously efficiency, system availability, fulfillment, privacy, contact, responsiveness, and compatibility of mobile device have significant influence on satisfaction by 40,90%. Partially only responsiveness and compatibility of mobile device which has significant influence on customer satisfaction. The result from this research also show that the customer satisfaction has significant influence on customer loyalty by 32,40%. According to the result, so Bank Rakyat Indonesia must increase their BRI Mobile service quality because it can influence customer satisfaction which will encourage their loyalty to always use BRI Mobile.